2022
DOI: 10.47482/acmr.2022.47
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of NLR, SII, and PLR in COVID-19 patient mortality and disease severity

Abstract: Background: In this study, it was aimed to evaluate the factors affecting the prognosis and mortality of patients hospitalized for coronavirus disease 2019 .Methods: Patients hospitalized with COVID-19 infection between March and November 2020 were examined retrospectively. The Systemic Immune-Inflammation Index (SII), platelet lymphocyte ratio (PLR), and neutrophil-lymphocyte ratio (NLR) values were evaluated for their effect on prognosis.Results: Of the 1013 patients included in the study, 204 (20.1%) had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…6 As they are one of the routine laboratory tests, they are noncostly, available, and easily measurable. 7 NLR can be utilised as a prompt warning indicator of severe COVID-19. 8 However, most previous studies were reported from China and, to a lesser extent, some countries in Europe, without concern for PLR.…”
Section: Introductionmentioning
confidence: 99%
“…6 As they are one of the routine laboratory tests, they are noncostly, available, and easily measurable. 7 NLR can be utilised as a prompt warning indicator of severe COVID-19. 8 However, most previous studies were reported from China and, to a lesser extent, some countries in Europe, without concern for PLR.…”
Section: Introductionmentioning
confidence: 99%